Hybrid diesel/PV system sizing and cost estimation - Belhamadia A.; Mansor M.; Younis M. (Institution of Engineering and Technology, 2023)
This paper presents a hybrid diesel/PV system cost study and sizing analysis for a hypothetical system in Kuala Terengganu, Malaysia. The hybrid generation is to support a 2MVA load as a standalone network. Diesel generator ratings followed the ISO 8528. The maximum size of the PV system is selected such that its penetration level does not exceed 25%. NEC 690 standards were followedin selecting the maximum and minimum numbers of modules. Cost estimation is carried out using Hybrid Optimization Model for Electric Renewable (HOMER). The results show that the mostefficient size of the PV system is 400kWpamong other alternatives and based on the connection configuration a theoretical maximum power of 387.6kWp would be generated from the system.